Karakterisasi Xilanase Streptomyces sp. ATG 70 yang Diproduksi Menggunakan Media Ekstrak Xilan Tongkol Jagung (Zea mays L.) - Tasya Preira Farrennina (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Xylanase is a hydrolytic enzyme that plays a role in xylan degradation and is widely used in various industries, suc as animal feed, food, bioenergy, and pulp and paper. Commercial production of xylanase is costly due to the use of commercial xylan substrates, so more economical and environmentally friendly substrate alternatives are needed. This study aims to determine the optimum pH of the production medium for Streptomyces sp. ATG 70 xylanase and characteristics of Streptomyces sp. ATG 70 produced using corn cob xylan extract media. Xylanase production was carried out through submerged fermentation with media pH variations of 4-8. The crude xylanase extract was then partially purified through ammonium sulfate precipitation and dialysis using a 10-14 kDa cellophane membrane. Enzyme characterization included determining the optimum pH, optimum temperature, and the effect of metal ions and EDTA on xylanase activity. The results showed that the highest xylanase production was obtained at a medium pH of 8 with an activity of 10.07±0.13 U/mL. Partial purification resulted in a 3.76-fold increase in specific activity compared to the crude extract. Streptomyces sp. ATG 70 xylanase had an optimum pH of 6 and an optimum temperature of 40˚C indicate that xylanase of Streptomyces sp. ATG 70 is neutral and mesophilic enzyme. Xylanase activity increased with the addition of Ca2+ and Cu2+ ions but was inhibited by EDTA, indicating that this enzyme is a metalloenzyme. These results demonstrate the potential for utilizing corn cob waste as an economical and sustainable alternative substrate for xylanase production. Keywords: corn cobs, characterization, Streptomyces sp. ATG 70, xylanase
Validasi file repositori 20 Juli 2026_Firli
Keywords: karakterisasi xilanase